PENGARUH EXPERIENTIAL MARKETING, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN STORE 3SECOND CILACAP - SRI HARTATI (Universitas Amikom Purwokerto, 2023)
Customer satisfaction is a feeling experienced by individuals in the form of pleasure that arises when the product purchased meets expectations. Conversely, if the product purchased does not meet consumer expectations, a feeling of disappointment or dissatisfaction will arise. This study examines the influence of Experiential Marketing, Service Quality and Product Quality on Customer Satisfaction at the 3Second Cilacap Store. The research analysis method uses classical assumption analysis, multiple regression, coefficient of determination, and t test. The sample used in the study was 96 people. Based on the research results using the t test on 3Second Cilacap Store customers, the results obtained from Experiential Marketing have a positive effect on Customer Satisfaction, Service Quality has a positive effect on Customer Satisfaction and Product Quality also has a positive effect on Customer Satisfaction 3Second Store Cilacap. This shows that if these three variables experience an increase, it will increase customer satisfaction with the 3Second Cilacap Store